2017
DOI: 10.1785/0120160296
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of High‐Rate GPS for Strong Ground Motion Assessment

Abstract: We show that high-rate Global Positioning System (GPS) can have a vital role to play in near-real-time monitoring of potentially destructive earthquakes. We do this by investigating the potential of GPS in recording strong ground motions from earthquakes in Switzerland and Japan. The study uses finite-fault stochastic groundmotion simulation based on Fourier amplitude spectra and duration models previously developed for both countries, allowing comparisons in terms of both Fourier and timedomain characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Previous studies have shown that 5 Hz GPS data can be used to recover a significant part of PGV values for large earthquakes [33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 5 Hz GPS data can be used to recover a significant part of PGV values for large earthquakes [33].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement noise z[k] is considered additive with zero mean, since constant bias is estimated by long term averaging and then subtracted from the measurement [5]. Hence, measured acceleration is expressed by (6). Consequently, measured displacement is shown by (7)- (9).…”
Section: A Noise Cancellation Using Zuptmentioning
confidence: 99%
“…By comparing the frequency contents of seismic and high-rate GPS data, Avallone et al [25] inferred that GPS sampling rates greater than 2.5 Hz are required in the near-field region of moderate-magnitude events to provide solutions for the coseismic dynamic displacement that are free of aliasing artifacts [28,29]. Therefore, high-rate GPS data recorded at a sampling rate of 10 Hz were selected for this study.…”
Section: High-rate Gps Recordsmentioning
confidence: 99%